The Influence of Green Accounting and Intellectual Capital on SRI-KEHATI Firms’ Sustainability (2018–2022) - I Ketut Suryanawa; Maria Mediatrix Ratna Sari; I Gusti Ayu Desni Saraswati Sudirga (AIBPM Publisher, 2025)
Sustainability has become a central concern in modern business practices, prompting organizations to integrate environmental responsibility and the management of intellectual resources into their performance strategies. However, empirical research linking green accounting and intellectual capital to sustainability performance, particularly in emerging markets, remains limited. This study examines the influence of green accounting and intellectual capital on the sustainability performance of companies listed in the SRI-KEHATI Index during the 2018–2022 period. Using a quantitative approach and purposive sampling, 17 companies were selected as the research sample. Multiple linear regression analysis was employed to assess the effect of the independent variables on sustainability performance. The results show that both green accounting and intellectual capital have a statistically significant positive influence on sustainability performance, with green accounting exhibiting a stronger effect (? = 0.421, p 0.05) compared to intellectual capital (? = 0.337, p 0.05). These findings affirm stakeholder and legitimacy theories, showing that environmental accountability and intangible resource management are vital for long-term sustainability, and that integrating them into strategy can boost financial, environmental, and social outcomes